Sweet and Sour: The Impact of Differential Glycosylation in Cancer Cells Undergoing Epithelial–Mesenchymal Transition - Freire-de-Lima, Leonardo (Frontiers in Oncology, 2014)
Glycosylation changes are a feature of disease states. One clear example is cancer cells, which commonly express glycans at atypical levels or with different structural attributes than those found in normal cells. Epithelial-mesenchymal transition (EMT) was initially recognized as an important step for morphogenesis during embryonic development, and is now shown to be one of the key steps promoting tumor metastasis. Cancer cells undergoing EMT are characterized by significant changes in glycosylation of the extracellular matrix (ECM) components and cell surface glycoconjugates. Current scientific methodology enables all hallmarks of EMT to be monitored in vitro and this experimental model has been extensively used in oncology research during the last ten years. Several studies have shown that cell-surface carbohydrates attached to proteins through the amino acids, serine, or threonine (O-glycans), are involved in tumor progression and metastasis, however, the impact of O-glycans on EMT is poorly understood. Recent studies have demonstrated that transforming growth factor-beta (TGF-β), a known EMT inducer, has the ability to promote the up-regulation of a site-specific O-glycosylation in the IIICS domain of human oncofetal fibronectin (onfFN), a major ECM component expressed by cancer cells and embryonic tissues. Armed with the knowledge that cell surface glycoconjugates play a major role in the maintenance of cell homeostasis and that EMT is closely associated with glycosylation changes, we may benefit from understanding how unusual glycans can govern the molecular pathways associated with cancer progression. This review initially focuses on some well-known changes found in O-glycans expressed by cancer cells, and then discusses how these alterations may modulate the EMT process.